Protective Effects of Citronellol Against Rhabdomyolysis-Induced Acute Kidney Injury in Mice by Inhibiting NF-κB and IL-1β - Yasmeen Nasrawi; Sermad Hashim Kadhim (College of Pharmacy University of Baghdad, 2023)
Objectives: acute kidney injury (AKI) is a serious pathophysiology side effect of rhabdomyolysis. Inflammatory mechanisms play a role in the development of rhabdomyolysis-induced AKI. Citronellol (CT) is a naturally occurring monoterpene alcohol (3,7-Dimethyl-6-often-1-ol) found in aromatic plant species' essential oils. In this study, we explored the protective effects of Citronellol on glycerol-induced AKI. Methods: Four groups of eight mice each (n=8) were formed by randomly dividing the animals into the groups, glycerol-induced AKI model group, low-dose CT-treated group (50mg/kg), high-dose CT-treated group (100mg/kg), and control group. The renal functions of mice from all groups were evaluated using serum urea and creatinine. Creatine kinase (CK) level was used to detect rhabdomyolysis. Inflammatory response was determined using Nf-kB and iL-1B levels. Results: Citronellol in both doses 50&100 mg/kg significantly decreased serum urea, creatinine and CK as Compared to the glycerol group, as well as treatment with citronellol resulted in a lower expression of both NF-κB and IL-1β in the renal tissue, indicating that citronellol may have an anti-inflammatory effect in AKI. Conclusion: prophylaxis with low and high doses of citronellol improved inflammatory responses and renal function. It's possible that by inhibiting Nf-kB and iL-1B, these positive effects were achieved, inhibiting the development of inflammatory cytokines as a result. These discoveries reveal fresh details regarding a potential treatment option for kidney injury caused by rhabdomyolysis.